Intervention design elements are associated with frontline health workers' performance to deliver infant and young child nutrition services in Bangladesh and Viet Nam (P10-128-19) - Nguyen, Phuong Hong; Kim, Sunny S.; Tran, Lan Mai; Menon, Purnima; Frongillo, Edward A. (Oxford University Press, 2019)
Frontline health workers (FLW) are needed for delivering interventions at scale to reduce maternal and child undernutrition, but low- and middle-income countries often face inadequate FLW performance. This study aimed to test whether and how intervention design elements such as training, supervision, and mass media improved FLW performance in delivering nutrition services.